Handbook of corrosion inhibitors - Ash, Michael (Synapse Information Resources, 2011)
This Handbook is designed to function as a selection tool for corrosion-inhibiting chemicals.
Keywords: Corrosion control industry.; Chemical inhibitors.; Protective coatings.; Protective coatings industry.; Corrosion and anti-corrosives.; elektronické knihy; electronic books